Pevnostní návrh příhradové prutové konstrukce - Rašovská, Hana (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2011)
Bakalářská práce se zabývá pevnostní, napjatostní a deformační analýzou rovinné příhradové konstrukce. Cílem práce je výpočet velikosti osových sil pro dvě uložení soustavy s následným návrhem geometrie průřezu. Uvažována je rovněž různá poloha břemene. Dále je posouzen vliv gravitačního pole Země a stanovena velikost posuvů v charakteristických místech konstrukce.

Bachelor thesis deals with strength, stress and strain analysis of the plain truss construction. The aim of the thesis is calculation the size of forces for two storage of the system with resultant suggestion of the cross- section geometry. The different position of the load is also considered. Further the influence of gravitational field of the Earth is reviewed as well as displacements in characteristic places, in construction is defined.
Strength design of the truss construction
Keywords: Napjatost; Deformace; Pevnostní kontrola; Prut; Příhradová konstrukce; Statická rovnováha; Styčník; Výztuha; Stress; Strain; Strength analysis; Beam; Truss construction; Static balance; Framework joint; Reinforcement